2017
DOI: 10.1152/jn.00437.2016
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of superior colliculus affects strabismus angle in monkey models for strabismus

Abstract: Disruption of binocular vision during the critical period for development leads to eye misalignment in humans and in monkey models. We have previously suggested that disruption within a vergence circuit could be the neural basis for strabismus. Electrical stimulation in the rostral superior colliculus (rSC) leads to vergence eye movements in normal monkeys. Therefore, the purpose of this study was to investigate the effect of SC stimulation on eye misalignment in strabismic monkeys. Electrical stimulation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
(54 reference statements)
2
16
0
Order By: Relevance
“…3 Recent data from animal models of strabismus acquired using neurophysiological methods such as electrical stimulation, muscimol inactivation, and single cell recording within numerous brain areas including the motor nuclei, supraoculomotor area (SOA), fastigial and posterior interposed nuclei of the cerebellum, paramedian pontine reticular formation (PPRF), and the superior colliculus (SC), have shown that various structures within a vergence neural circuit contributes toward maintenance of the state of strabismus. [4][5][6][7][8][9][10][11] The SC has been extensively studied for its involvement in saccadic eye movements, [12][13][14] and this structure also appears to have a role in vergence. Van Horn et al, 15 in a study in normal monkeys, have shown that the rostral SC (rSC) contains vergence related neurons (convergence and divergence), which modulate with eye movements made to sinusoidal target motion in depth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Recent data from animal models of strabismus acquired using neurophysiological methods such as electrical stimulation, muscimol inactivation, and single cell recording within numerous brain areas including the motor nuclei, supraoculomotor area (SOA), fastigial and posterior interposed nuclei of the cerebellum, paramedian pontine reticular formation (PPRF), and the superior colliculus (SC), have shown that various structures within a vergence neural circuit contributes toward maintenance of the state of strabismus. [4][5][6][7][8][9][10][11] The SC has been extensively studied for its involvement in saccadic eye movements, [12][13][14] and this structure also appears to have a role in vergence. Van Horn et al, 15 in a study in normal monkeys, have shown that the rostral SC (rSC) contains vergence related neurons (convergence and divergence), which modulate with eye movements made to sinusoidal target motion in depth.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical stimulation not only evoked staircase saccades but also produced a divergent change in strabismus angle as we have shown in our previously published study. 7 The small amplitude of the electrically evoked saccade at the two sites (panels A-ii [mean: 0.38 6 0.18] and B-ii [mean: 3.68 6 0.38]) indicate that these cells were located in the rostral part of the SC. 12 In these data, the strabismus angle (left eye position -right eye position) is modulated depending on which of the two eyes is fixating (panels A-iii and B-iii), and this property was leveraged to investigate the correlation between strabismus angle and neural response rate within the subpopulation of rSC cells.…”
Section: Sc Cell Responses Associated With Change In Strabismus Anglementioning
confidence: 99%
See 2 more Smart Citations
“…Neurons within the supra-oculomotor area, which encodes vergence responses in normal animals, were found to encode horizontal misalignment in strabismic monkeys (Das 2012). More recent studies showed that electrical stimulation of the rostral superior colliculus causes a change in strabismus angle (Fleuriet et al 2016) (Upadhyaya et al 2017). Given the weight of evidence supporting a neural substrate for maintenance of strabismus, it is likely that neural plasticity following surgical manipulation of the EOM also contributes to the final strabismic state achieved after surgery.…”
Section: Introductionmentioning
confidence: 99%